When Politics is more than Words: A Hermeneutic Analysis of Freudian Psychoanalytic Elements among selected Philippine Presidential State of the Nation Addresses (SONA) - Sy, Andrea Nicole; Yson, Mary Louise Beatrix; Gavino, Nikolai; De Leon, Michael Warren; Ocampo, Jonathan; Calilung, Froilan (Advances in Social Sciences Research Journal, 2019)
Not Available